Studi Anatomi Lambung Kelelawar Buah (Pteropus vampyrus) Dengan Pewarnaan Histokimia Periodic Acid Shiff (PAS) - George Marthienz do Hage; Yulfia Nelymalik Selan; Filphin Adolfin Amalo (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Timor Island, East Nusa Tenggara (NTT) has a large enough population of bats. A fruit bat (Pteropus vampyrus) is one of such species. Gastric in mammals consist of three region that is fundus, cardia and pylorus. This study aims to determine whether there are differences in the distribution pattern of constituent cells of gastric in Pteropus vampyrus to other mammals. Pteropus vampyrus is anaesthetized with ketamine 20 mg/kg and xylazine 2 mg/kg intramuscularly. In the anesthetized state, the perfusion of the heart is done by opening the chest cavity. Further observation is to the gastric in macroanatomy and then gastric organs were fixed by 10% formalin and then stain with histochemical staining (PAS). Region of Fundus of the stomach area occupies most of the region compared to the cardia and pylorus. Cardia and pyloric region are dominated by the parietal cells and mucous neck cells on the surface, but the pyloric region has begun to form gastric pits. Fundus region is dominated by the constituent cells such as gastric chief cells and parietal cells. Based on the results of the study, it is concluded that the distribution pattern in Pteropus vampyrus chief cells, parietal and mucous neck cells are different from other mammals.